Effect of alloying in monolayer niobium dichalcogenide superconductors - Mazin, I.I (Nature Research, 2022)
When sulfur and silicon are incorporated in monolayer 2H-NbSe2 the superconducting transition temperature, Tc, has been found to vary non-monotonically. This was assumed to be a manifestation of fractal superconductivity. Using first-principles calculations, we show that the nonmonotonic dependence of Tc is insufficient evidence for multifractality. A unifying aspect in our study are selenium vacancies in NbSe2, which are magnetic pair-breaking defects that we propose can be present in considerable concentrations in as-grown NbSe2. We show that sulfur and silicon can occupy the selenium sites and reduce the pair-breaking effect. Furthermore, when sulfur is incorporated in NbSe2, the density of states at the Fermi level and the proximity to magnetism in the alloy are both reduced compared to the parent compound. Based on our results, we propose an alternative explanation of the non-monotonic change in Tc which does not require the conjecture of multifractality. © 2022, This is a U.S. Government work and not under copyright protection in the US; foreign copyright protection may apply.